2016
DOI: 10.5688/ajpe80463
|View full text |Cite
|
Sign up to set email alerts
|

Education and Assessment of Pharmacists on the Use of the Drug Burden Index in Older Adults Using a Continuing Professional Development Education Method

Abstract: Objective. To educate pharmacists and assess their knowledge of and ability to calculate the Drug Burden Index (DBI) using a continuing professional development (CPD) intervention. Methods. The intervention included designing education surrounding the DBI and its application in practice and assessing knowledge in the form of a CPD education article with four multiple-choice questions (MCQs). Deidentified demographic data on participants were collected. Results. Multiple-choice questions were completed by 2522 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…An example of alternate substrate inhibition is observed with paroxetine as its methoxy diene carbon moiety was found to be responsible for the formation of covalent bonds at the active site of CYP2D6 [21,22]. Another example of this type of inhibition was observed with clarithromycin when the nitrosoalkene intermediate generated by N-demethylation forms covalent bonds with the active site of CYP3A4 [23].…”
Section: Mechanism-based Inhibitionmentioning
confidence: 99%
“…An example of alternate substrate inhibition is observed with paroxetine as its methoxy diene carbon moiety was found to be responsible for the formation of covalent bonds at the active site of CYP2D6 [21,22]. Another example of this type of inhibition was observed with clarithromycin when the nitrosoalkene intermediate generated by N-demethylation forms covalent bonds with the active site of CYP3A4 [23].…”
Section: Mechanism-based Inhibitionmentioning
confidence: 99%
“…Given the importance of self‐medication in many allergic diseases and in iatrogenic disease, pharmacist interventions are well placed to maximize the benefits and minimize the adverse events associated with pharmacotherapy. This is particularly important in AR and asthma multimorbidity as well as in the elderly patients, a large number of whom present with allergic diseases in combination with other chronic diseases . Moreover, most AR medications are available over‐the‐counter (OTC) .…”
Section: Pharmacist Challenge In Allergic Rhinitismentioning
confidence: 99%
“…For example, passive interventions such as printed educational material are commonly used [ 11 ]. A study by Kouladjian et al [ 12 ] reported that journal articles are appropriate for educating pharmacists on estimating drug burden index, a measure of the total exposure to medications with anticholinergic and sedative properties. However, pharmacists may prefer more active interventions such as computer-based education [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%